Evaluation of Thyroid‐Stimulating Hormone, Total Thyroxine, and Free Thyroxine Concentrations in Hyperthyroid Cats Receiving Methimazole Treatment. (1st April 2015) - Aldridge, C.; Behrend, E.N.; Martin, L.G.; Refsal, K.; Kemppainen, R.J.; Lee, H.P.; Chciuk, K.
<x xml:space="preserve">Abstract</x> Background Iatrogenic hypothyroidism (IH) after treatment of hyperthyroidism can impair renal function. No study compared the efficacy of measurement of serum free thyroxine by equilibrium dialysis (fT4ed) or thyroid‐stimulating hormone (TSH) concentrations for monitoring cats receiving methimazole. Objectives To (1) compare the ability of total T4 and fT4ed concentrations in conjunction with TSH to define thyroid function in hyperthyroid cats receiving methimazole, (2) determine the prevalence of IH in cats receiving methimazole, and (3) examine the relationship between thyroid axis hormones and serum creatinine concentration. Animals One hundred and twenty‐five serum samples from hyperthyroid cats receiving methimazole and total T4 concentrations ≤3.9 μg/dL. Methods Total T4, fT4ed, and TSH concentrations were measured to evaluate thyroid status and serum creatinine concentration was measured to assess renal function. A low total T4 or fT4ed concentration in combination with an increased TSH concentration defined IH. Results Forty‐one cats (33%) had increased TSH concentrations. Of cats with total T4 and fT4ed concentrations below the reference range, 68% and 73%, respectively, had TSH concentrations above the reference range. Only 18% of cats with a normal TSH concentration had an increased serum creatinine concentrations as compared to 39% of those with increased TSH concentrations (P < .001). Conclusions Free T4ed does not identify more cats with potential IH as compared to total T4. The IH prevalence was approximately 20%. Measurement of TSH may be more helpful in indicating that azotemia, if present, is at least in part related to IH. Investigation is needed to define TSH assay utility in identifying possible subclinical IH.